Policies Matter: Tendencies towards Academic Misconduct - Erçin, Nalan; Razi, Salim (Canadian Perspectives on Academic Integrity, 2021)
Upon the breakout of COVID-19 around the world in March 2020 and due to the threat of its spread, the mode of teaching has been shifted. This sudden influx to online education is named as Emergency Remote Teaching (ERT – Hodges et al., 2000). Technology-based academic integrity infringements are affiliated with the utilization of the internet for getting aid in taking exams, plagiarizing, taking an exam on behalf of others and many more (Etter et al., 2006). This study aimed to explore students’ perception of academic misconduct through the hypothetical scenarios adapted from Lozier (2012) and individual and focus group interviews focused on three concepts: the self-evaluation as a student, the sanctions of the academic misconduct policies, the perception of the academic integrity promotion provided by the lecturers in the light of these research questions: Do the participants consider examples of a) contract cheating b) collision c) plagiarism as cheating? How serious do the participants consider the scenarios of academic misconduct? Have the participants witnessed a) contract cheating b) collision c) plagiarism? Do the participants’ perceptions of a) contract cheating b) collision c) plagiarism as cheating vary by gender significantly? What is the participants’ perception relevant to the rise or the fall of academic integrity transgression during ERT? What are the participants' perceptions regarding the sanctions of academic misconduct and integrity promotion acts provided by the institution where they study? The study was carried out in one of the public universities located in the west of Turkey called Kocaeli University (KOU), in the School of Foreign Languages (KOU SLF) in the spring term of the 2020- 2021 academic year. The participants (N=234) were the students who learned English as a foreign language EFL). The demographic features of the participants were as follows: 147 participants were female while male participants were 87 and their ages ranged from 18 to 24. Specifically, of the 234 participants, a total of 18 participants volunteered to take part in the interview. The participants’ departments were various. The questionnaire consists of twelve (12) scenarios, and contract cheating, plagiarism, collision are the academic misconduct types employed in these hypothetical scenarios. The data collected through the questionnaire from 234 participants were analyzed with the help of SPSS (Statistical Package for Social Sciences, version 25.0). Of the findings, in the light of the mean values, plagiarism scenarios were regarded as academic misconduct, contract cheating is followed by collusion scenarios. Similarly, plagiarism scenarios were considered as the most serious academic integrity transgression, while collusion scenarios were taken as the least serious academic misconduct by the participants. The findings of the third research question were consistent with the findings of the first two research questions; that is to say, the participants reported that they had witness collusion more than any other academic misconduct forms. The focus of the fourth research question was the gender variation towards academic misconduct, and the findings revealed that the female participants showed a tendency to regard the cases in the scenarios as academic misconduct. In contrast, the male participants did not consider the cases in the scenarios as academic misconduct as much as their female counterparts. The focus group interviews conducted with the three different groups of six students revealed that all participants reported that if the system had the gaps allowing academic misconduct, they would benefit from these gaps. And taking an exam for somebody else was the most common academic misconduct form among the students.